Perilaku Menunda Pernikahan pada Wanita Korban Perceraian Orang Tua - Agusriyani, Intan; Afdal, Afdal (TSAQOFAH, 2026)
Marriage is regarded as a crucial phase in the life cycle; however, some women choose to postpone marriage, one contributing factor being childhood experiences marked by parental divorce. Such experiences can shape negative perceptions of marriage and affect their emotional readiness to build a family. This study aimed to identify the reasons why women postpone marriage and to analyze the views of women who have experienced parental divorce regarding marriage. The study employed a qualitative approach with a phenomenological method. The research subjects were unmarried women aged 25–30 years from divorced families, selected using purposive sampling. Data were collected through observation, interviews, and documentation, and were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the reasons women who have experienced parental divorce postpone marriage include: (1) fear and trauma resulting from their parents’ divorce; (2) a lack of trust in the opposite sex; and (3) the absence of healthy marital role models. These findings affirm that the experience of parental divorce significantly influences how women perceive marriage and shapes their decision to delay it, underscoring the importance of adequate psychosocial support from families, counselors, and educators in the process of recovery and strengthening women’s readiness for marriage.